KIF20A silence inhibits the migration, invasion and proliferation of non‐small cell lung cancer and regulates the JNK pathway. (22nd October 2019) - Xie, Feng; He, Chengyan; Gao, Shen; Yang, Zhaowei; Li, Lihong; Qiao, Lu; Fang, Ling
Abstract: An increasing number of studies have shown that kinesin family member 20A (KIF20A) was overexpressed in several types of cancer, and its overexpression correlated with the oncogenesis and prognosis of cancers. However, little is known about the roles of KIF20A in human non‐small cell lung cancer (NSCLC). Thus, the aim of the present study was to demonstrate the expression of KIF20A in human NSCLC and reveal its biological functions and the underlying mechanisms. qRT‐PCR, western blot and immunohistochemistry were used to assess the expression of NSCLC patient specimens and NSCLC cell lines. The functions of KIF20A in migration and invasion were determined using Transwell assay. Cell proliferation capacity was performed by CKK‐8 assay. We demonstrated that KIF20A was overexpressed in NSCLC specimens compared with the adjacent non‐tumorous specimens, and high expression of KIF20A was associated with clinical stage and metastasis in NSCLC. Decreased expression of KIF20A inhibited NSCLC cells migration, invasion and proliferation. Most importantly, further experiments demonstrated that decreased the expression of KLF20A significantly downregulated expression of p‐JNK and MMP7, which indicated that knockdown of KIF20A alters lung cancer cell phenotype and regulates JNK pathways. These results suggest that KIF20A may act as a putative oncogene and a potential therapeutic target in NSCLC.